Assessment of pulmonary function of industrial workers in four different industries of Gujarat - Jani, Chinmay; Jain, Kushboo; Joshi, Arpita; Bala, D. V.; Jadav, Harshal; Jetpariya, Divyesh (International Journal Of Community Medicine And Public Health, 2019)
Background: Industrial workers working in various industries have exposure to different kind of pollutants. Exposure to various types of dust causes pneumoconiosis, a rising cause of impairment in factory workers. This study sought to analyze the effect of quantity and quality of dust variety and the duration of exposure on the pulmonary function test of the workers. Methods: Pulmonary function testing (PFT) was done using PC based spirometer in 4 different industries of Ahmedabad and Gandhinagar cities. The PFT values obtained were compared with normal values and the number of workers with impaired PFT was found. Associations were observed between types and amount of exposure with pulmonary impairment. Results: Out of 909 workers, 408 (44.88%) had pulmonary impairment of which 330 (80.88%) presented with restrictive lung function. It was found that maximum restrictive lung functions were found in workers exposed to metallic dust (51.4%) followed by metallic gases (43.8%). Whereas office administrative workers not having any direct exposure were having less impairment (p<0.005). Also, with increased duration of work in the industry, pulmonary impairment was also increasing. (χ2=119.89; p<0.005). Conclusions: Exposure to various types of dust impairs lung functions. The severity increases with the increase in the amount and duration of exposure. Proper protective measures should be taken by the workers and regular check-ups should be done to know any pulmonary impairment. The workers with impairment should be removed from exposure and relocated.